Assessment of the Diagnostic Skills of General Dentists in Different Types of Orthodontic Malocclusions - (:unkn) unknown (AVES, 2021)
Objective: One of the biggest problems in publicly funded dental clinics is the patient waiting list. The appropriate referral plays a key role in avoiding an increase in the number of patients on this waiting list. This study aimed to assess general dentists' diagnostic skills and approaches for different malocclusions. Methods: A questionnaire was prepared using photos of 8 patients previously treated for different malocclusions. One hundred twenty general dentists (83 female, mean age: 24 +/- 1.18 years; 37 male, mean age: 24 +/- 1.95 years) participated in the survey and were asked to decide whether the patient needed orthodontic treatment or orthognathic surgery, and to provide the reason for surgery (irregular teeth, or both unesthetic profile and irregular teeth), and the cause of the unesthetic profile (mandibular protrusion, mandibular retrusion, maxillary protrusion, maxillary retrusion). Results: The answers suggesting the need for orthodontic treatment were significantly higher for all malocclusions except for the Class II camouflage case. Of the Class III cases, the general dentists chose orthognathic surgery for both surgery and facemask cases (93.1%, 66.4% respectively). For the severe open bite case, orthognathic surgery was chosen with a ratio of 81.2%, and orthognathic surgery was decided as not necessary for the mild open bite case (74.8%). Among the surgery cases, mandibular retrusion for the Class II case (94.6%), mandibular protrusion for Class III case (95.4%), and maxillary retrusion for the severe open bite case (44.6%) were the maximum reported reasons. Conclusion: The distinction between camouflage and surgical treatment was better made by dentists in Class II and open bite cases than in Class III cases.
Keywords: Diagnosis; referral; malocclusion; TREATMENT NEED; AESTHETIC COMPONENT; FACIAL ATTRACTIVENESS; DENTAL AESTHETICS; INDEX; PERCEPTIONS; PRACTITIONERS; COMPLEXITY; RESIDENTS; STUDENTS